Perfectionism and Contingent Self-Worth in Relation to Disordered Eating and Anxiety. Issue 3 (May 2017) - Bardone-Cone, Anna M.; Lin, Stacy L.; Butler, Rachel M.
Abstract: Perfectionism has been proposed as a transdiagnostic risk factor linked to eating disorders and anxiety. In the current study, we examine domains of contingent self-worth as potential moderators of the relationships between maladaptive perfectionism and disordered eating and anxiety using two waves of data collection. Undergraduate females ( N = 237) completed online surveys of the study's core constructs at two points separated by about 14 months. At a bivariate level, maladaptive perfectionism was positively associated with disordered eating and anxiety. Maladaptive perfectionism and both appearance and relationship contingent self-worth interacted to predict increases in disordered eating. Neither of the interactive models predicted change in anxiety. Findings highlight maladaptive perfectionism as a transdiagnostic construct related to both disordered eating and anxiety. Interactive findings suggest that targeting maladaptive perfectionism and contingent self-worth (appearance, relationship) in prevention and treatment efforts could mitigate risk for the development or increase of disordered eating. Highlights: Perfectionism and contingent self-worth moderator models were examined. Disordered eating and anxiety were DVs in change analyses across 14 months. Maladaptive perfectionism was a risk factor for both disordered eating and anxiety. Maladaptive perfectionism and 2 forms of contingent self-worth interacted to predict increased disordered eating.